Tears of The Retinal Pigment Epithelium – A Review - Anika Gupta; Mohit Chhabra; Parth Mehta; Basudeb Ghosh (Delhi Journal of Ophthalmology)
Tears of the retinal pigment epithelium (RPE) may occur in eyes with a large pigment epithelial detachment (PED). They are most commonly associated with vascularized RPE detachment due to age-related macular degeneration (AMD) and usually involve a deleterious loss in visual acuity. With the extensive use of anti-vascular endothelial growth factor (anti-VEGF) therapy for treatment of eyes with neovascular AMD, recently there has been an increase in the incidence of RPE tear. Multimodal retinal imaging techniques help in accurate detection of RPE tears and help in identifying eyes with high risk factors for RPE tears formation. Understanding the pathogenesis and risk factors of RPE tears is important for better management of these eyes as RPE tears are associated with poor visual prognosis, especially if the fovea is involved. This review summarizes the current knowledge on RPE tear pathogenesis, risk factors for an impending tear, and approach to management of these eyes before and after RPE tear formation